Targeting in development projects in Egypt: Approaches, challenges, and lessons learned - Shokry, Nada; Jovanovic, Nina; Kurdi, Sikandra; Hamdy, Adham; Elkaramany, Mohamed (International Food Policy Research Institute, 2024)
Effective targeting strategies are vital for almost all development programs. Universal approaches which provide aid to all individuals regardless of need are not always feasible given limited budgets and varying development priorities. Conversely, targeting directs resources to those in greatest need, ensures efficient allocation while upholding principles of social justice, equality, and the right to assistance.